Talus reconstruction using fresh structural allograft after nontraumatic avascular necrosis: case report - Fuentealba Pooley, Andres; Henriquez Sazo, Hugo; Lagos Sepulveda, Leonardo; Bastias Soto, Christian; Vargas Gallardo, Fernando; Fernandez Comber, Sergio (Journal of the Foot & Ankle, 2021)
Avascular necrosis of the talus is a rare condition that can lead to important functional sequelae. There are few therapeutic alternatives for more advanced stages of this disease, the majority of which sacrifice the ankle joint. We report the case of a 50-year-old patient with nontraumatic avascular necrosis that compromised a large part of the talar surface. After non-structural autograft failed, it was reconstructed using fresh structural talar allograft. At one year of follow-up, the patient reported a considerable decrease in pain. To our knowledge, this is the first reported case in which fresh structural allograft was used in the treatment of nontraumatic avascular necrosis of the talus. Level of Evidence V; Therapeutic Studies; Expert Opinion.